Detection and Tertiary Treatment Technologies of Poly-and Perfluoroalkyl Substances in Wastewater Treatment Plants - Araújo, Rafael G.; Rodríguez-Hernandéz, Jesús A.; González-González, Reyna Berenice; Macias-Garbett, Rodrigo; Martínez-Ruiz, Manuel; Reyes-Pardo, Humberto; Hernández Martínez, Saúl Antonio; Parra-Arroyo, Lizeth; Melchor-Martínez, Elda M.; Sosa-Hernández, Juan Eduardo; Coronado-Apodaca, Karina G.; Varjani, Sunita; et al. (Frontiers in Environmental Science, 2022)
PFAS are a very diverse group of anthropogenic chemicals used in various consumer and industrial products. The properties that characterize are their low degradability as well as their resistance to water, oil and heat. This results in their high persistence in the environment and bioaccumulation in different organisms, causing many adverse effects on the environment as well as in human health. Some of their effects remain unknown to this day. As there are thousands of registered PFAS, it is difficult to apply traditional technologies for an efficient removal and detection for all. This has made it difficult for wastewater treatment plants to remove or degrade PFAS before discharging the effluents into the environment. Also, monitoring these contaminants depends mostly on chromatography-based methods, which require expensive equipment and consumables, making it difficult to detect PFAS in the environment. The detection of PFAS in the environment, and the development of technologies to be implemented in tertiary treatment of wastewater treatment plants are topics of high concern. This study focuses on analyzing and discussing the mechanisms of occurrence, migration, transformation, and fate of PFAS in the environment, as well the main adverse effects in the environment and human health. The following work reviews the recent advances in the development of PFAS detection technologies (biosensors, electrochemical sensors, microfluidic devices), and removal/degradation methods (electrochemical degradation, enzymatic transformation, advanced oxidation, photocatalytic degradation). Understanding the risks to public health and identifying the routes of production, transportation, exposure to PFAS is extremely important to implement regulations for the detection and removal of PFAS in wastewater and the environment.